Penerapan Akuntansi Lingkungan Terhadap Keberlanjutan Menggunakan Perspektif Pentuple Bottom Lines Pada PG. Modjopanggoong - Salsa Amalia Maghfiroh (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine how the application of the environmental accounting to sustainability using the perspective of the pentuple bottom lines and to determine how PG. Modjopanggoong overcomes the challenges and obstacles faced in the application of environmental accounting to the sustainability using the perspective of the pentuple bottom lines. This study uses a qualitative descriptive method with a pentuple bottom lines perspective which includes five aspects, namely people, profit, planet, prophet, and phenotechnology. The results of the study indicate that in the application which since from "People" aspect, PG. Modjopanggoong tries to create a safe, a decent and conducive working environment for its employees and ensure the welfare of the community around the company's environment. While seing from the "Profit" aspect, PG. Modjopanggoong shows that the company understands of the importance in maintaining the competitive, the advantage, the quality and the innovation of the products produced. In the "Planet" aspect, PG. Modjopanggoong shows awareness in maintaining and creating a clean environment. In the "Prophet" aspect, PG. Modjopanggoong has applied the transcendental concept to both employees and the community around the company's environment. In the "Phenotechnology" aspect, PG. Modjopanggoong has implemented the use of hardware, software, networks, telecommunications and databases in its operational activities.